The State of Electronic Data Wall Usage on E-learning platforms from the Perspectives of Middle School Female Teachers - Alluhaybi, Muslihah Rashed; Sobahi, Rana Atif (Journal of Educational and Psychological Sciences, 2023)
The research aimed to examine the reality of implementing the data wall platform from the perspective of middle school female teachers and the extent of using data wall systems to achieve digital transformation and the challenges of their use. To achieve the research objectives and answer the research questions, the study adopted a descriptive-analytical approach to explore the perspectives of middle school female teachers regarding the use of data walls. An electronic questionnaire was designed and administered to a sample of (90) female teachers in the middle school stage in Mecca. The research results showed that the implementation of the data wall in the educational process from the perspective of middle school female teachers was highly regarded, with an average score of (4.01) and a relative weight of (80.3%). The importance of the data wall axis ranked first with an average score of (4.06) and a relative weight of (81.2%), while the concept and implementation of the data wall axis ranked second with an average score of (3.97) and a relative weight of (79.3%). The challenges of implementing the data wall axis ranked third with an average score of (3.91) and a relative weight of (78.2%). The results also yielded a set of recommendations for implementing digital data wall platforms in middle school settings.
Keywords: date wall; Students’ achievement; Students’ Evaluation; Electronic Systems